IN VITRO STUDIES OF BIOMATERIAL DEVICE HYDROXYAPATITEâ€ PREPARED FROM DIFFERENT ROUTES FOR BIOMEDICAL APPLICATIONS - Rasool, Ishfaq; Singh, Anjuvan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Biomaterial devices are used to replace any damaged or destroyed parts of the human body. Our body tissue and bone perform for an extended period of time, but sometimes they do suffer from a kind of destructive processes, including infection, fracture, or loss of function. The objective of our study is to solve the existing problem, as it may be possible to get rid of the diseased tissue and put back it with some suitable synthetic material. Methods: A new versatile and economic method is used for the synthesis of hydroxyapatite (Hap). In this method, the effect of three different stirring techniques (ultrasonic, magnetic, and double-step stirring) on the properties of hydroxyapatite was investigated. Synthesis of hydroxyapatite by different methods was confirmed by Fourier transform-infrared (FT-IR), X-ray diffraction (XRD), and scanning electron microscopy analysis. An in vitro study of synthesized hydroxyapatite was done to test for biocompatibility. Results: Pure white and crystalline hydroxyapatite was obtained by the chemical precipitation method as it was confirmed through XRD and FTIR analysis. It was confirmed that hydroxyapatite synthesized using sonication and magnetic stirring method was pure and stable in nature. The bioactivity evaluation of synthesized hydroxyapatite was done using biodegradation tests and by its interaction with the peripheral blood mononuclear cells. Conclusion: Hydroxyapatite was synthesized successfully by bringing variation in process parameters using a chemical precipitation method. To prove for biocompatibility behavior of synthesized biomaterial bioactivity and biodegradation test was done successfully.